THE EFFECT OF REARING SYSTEM AND ENVIRONMENTAL TEMPERATURE IN CLOSED HOUSES ON THE ‎LAYING PERFORMANCE - A.A. Naji, Saad,; A. Al-Kaissy, G.; A. Al-Attar‎, H.; H.‎ Ismail‎, I. (The Iraqi Journal of Veterinary Medicine, 2024)
A study wes conducted on the effect of two rearing systems (Cages and floor) and the environmental temperature on the egg production and mortality percent , of the laying hens. A total of 6000 Hisex Brown laying hens, 22 weeks old, were randomly divided in two closed houses. Hens in the first house were raised in cages while hens in the second house were raised on the floor, All birds were fed ad. Libitum a commertial laying diet. One year experiment was divided into 13 periods of 4 weeks each. At the end of each period, H.D, H.H. egg production and mortality percent were calculated The data indicated, that rearing system did not significantly affect the egg production of the laying hens, but the mortality percent were significantly (P<0.05) decreased in caged hens. Environmental temperature seemed not to affect the egg production, and a positive correlation and regrasion coefficients were found between environmental temperature and egg production.